Pengaruh Strategi Promosi Stikom Interstudi terhadap Peningkatan Ekuitas Merek - Soebiagdo Soebiagdo; Poppy Ruliana (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2017)
The purpose of this study is to determine and analyze the influence of STIKOM InterStudi promotion strategy to increase brand equity. The concept of promotional strategy according to Lamb, Hair, McDaniel (2001: 146), is a plan for optimal use of elements of advertising, public relations, personal sales and sales promotion